Mario Botta [videorecording] : the shape of a story = centre durrenmatt - Kuert, Beat; Kerr, Charlotte; Al Castello SA (Arzo, Switzerland : Al Castello SA, 2001)
One year after Friedrich Durrenmatt's death, his wife Charlotte Kerr asks Mario Botta to create a museum for Durrenmatt's paintings. The Centre Durrenmatt in Neuchatel is opened to the public in September 2000. The small museum hosts the graphic and pictorial work of the famous writer, which has always been an integral part of of his life. The structure emanates the strong synergy present between Botta's architecture and the writer's philosophy. Certain areas - like the one dedicated to the Minotaur and the labyrinth - show a strong complicity and dialogue between the two artists